The Establishment of ASEAN Framework of Action on Marine Debris: The Role of Shared Knowledge - Putri, Rizky Anggia; Hudaya, Maula (Global: Jurnal Politik Internasional, 2022)
Since the 1970s, marine debris pollution has been considered a global environmental problem because of the serious threat it poses. Based on 2010 data, the amount of marine debris pollution from the four ASEAN countries plus China has exceeded a quarter of the total global pollution. In 2015, the Sustainable Development Goals (SDGs), in particular the 14th goal regarding life under water, were implemented to address this issue in the global realm. But regionally, ASEAN as the biggest pollutant has just formed the ASEAN Framework of Action on Marine Debris in 2019. The time lag is large considering the urgency to respond has emerged since 2010. Even since 2011, ASEAN countries have started research and individual handling efforts. Therefore, knowledge about this issue has emerged since the early 2010s. However, this knowledge does not necessarily get the attention of ASEAN to deal with it collectively. We see that there is an unexplained link between the emergence of urgency and knowledge regarding marine debris pollution in the early 2010s and the formation of the regime in 2019. In this paper, we attempt to analyze how this urgency and knowledge ultimately gained the attention of ASEAN and ultimately formed the regime. The analysis will be carried out using the Weak Cognitivism approach in Knowledge-based theory, focusing on the role of the epistemic community in creating shared knowledge as the key to the formation of an international regime.